Pengaruh Penerapan Metode Talaqqi terhadap Keberhasilan Hafalan Al-Qur’an - Qhotimah, Qusnul; Nashir, Muhammad Ja’far; Gunawan, Herri (MODELING: Jurnal Program Studi PGMI, 2023)
Basically the purpose of education is to produce generations of people who believe and fear God Almighty. In Islam, one of the ways to increase your faith and devotion to Allah SWT is by studying and memorizing the Al-Qur'an. Of the many different methods used for studying the Qur'an, one of which is the talaqqi method. The talaqqi method aims to facilitate students in learning and memorizing the Qur'an. In articles This paper will discuss the effect of the application of the talaqqi method on the success of memorizing the Al-Qur'an. Which is where this study aims to determine whether there is any effect of applying the talaqqi method to the success of memorizing the Al-Qur'an. This study uses a quantitative approach with research subjects at the Basic Level Tahfidzul Qur'an Islamic Boarding School Tarbiyatul Ummah Sukoharjo. The independent variable (Variable X) in this study is the application of the talaqqi method, while the dependent variable (Variable Y) is memorizing the Al-Qur'an. The results of this study indicate that the application of the talaqqi method is quite good with a percentage of 94.4%. The results of testing the hypothesis using the sig. (2-tailed) obtained a small significance value from the probability value (0.000 <0.05), obtained a Pearson Correlation value of 0.0856 and it can be said to be positive based on the known t value of the calculation results of 0.840 or 0.856 > 0.840, so it can be concluded that the variable X affects variable Y.